Carcass characteristics of intensively fed finisher lambs maintained on varying plane of nutrition in pre -weaning phase - KARIM, S A; SANTRA, A; SEN, A R; SHARMA, V K (The Indian Journal of Animal Sciences, 2014)
The impact of pre weaning plane of nutrition (high, G1; medium, G2; low, G3) on post-weaning growth and carcass characteristics of finisher lambs was evaluated. The weaning weights were 14.3, 13.0 and 14.8 kg in GI, G2 and G3, respectively, while the finishing weight was higher (P< 0.01) in the G3 (24.8 kg), maintained on low plane of nutrition in pre weaning phase, than G1 (21.9 kg) or G2 (21.0 kg). The pre slaughter weight, empty live weight, hot carcass weight with kidney and kidney fat and hot carcass weight with edible offal were higher (P<0.01) in Gland G3 than G2 lambs. The dressing percentage on pre slaughter was higher in Gland G3 than G2 while dressing yield in terms of empty live weight was similar in the 3 groups. Total inedible and edible offal weights were lower in G2 than G I and G3, whereas in terms of empty live weight, the yields were similar in the 3 groups. Dissected lean, fat and bone content of the half carcass were similar in the 3 groups. The per cent distribution of the primal cuts in half carcass, viz. leg, loin, rack. neck and shoulder and breast and fore shank were also similar. G3 lambs deposited more depot fat, particularly as kidney fat than other 2 groups. It is concluded that the lambs maintained on low plane of nutrition in pre- weaning phase showed compensatory growth improvement in post- weaning stage under intensive feeding and deposited more carcass and depot fat.